Realization of large transmitted optical Goos–Hänchen shifts in photonic crystal slabs - Du Shihao; Zhang Wenjie; Liu Wenzhe; Zhang Yanbin; Zhao Maoxiong; Shi Lei (Nanophotonics, 2022)
In this letter, we demonstrate the existence of large transmitted optical positive and negative Goos–Hänchen shifts in photonic crystal slabs numerically and experimentally. The Goos–Hänchen shift we observed directly reaches ∼20 μm, which is 30 times the wavelength, approaching the radius of the beam waist. To explain this phenomenon, we measure the transmission phase through the phase measurement system and find there is an acute phase change near the resonance in photonic crystal slabs, which enhances the Goos–Hänchen shift. Our experimental results are consistent with simulation, and the work can be used to modulate the propagation of light in further research.